2022
DOI: 10.1002/arch.21911
|View full text |Cite
|
Sign up to set email alerts
|

Electroantennographic activity of 21 aliphatic compounds that bind well to a locust odorant‐binding protein

Abstract: Odorants that bind well to odorant‐binding proteins (OBPs) often trigger olfactory responses and have important biological significance. The locust Locusta migratoria (Meyen) (Orthoptera: Acrididae) is a serious agricultural pest. Twenty‐one saturated aliphatic compounds with carbon–oxygen bonds and straight chains of 10–17 carbon atoms bind well to an L. migratoria OBP. In this study, olfactory activities of these aliphatic compounds on L. migratoria adult males were tested by electroantennography (EAG) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…A living host of a particular insect can vary greatly based on its life history and feeding guilds, ranging from plants to other animals or humans. Insect OBPs involved in the recognition of host semiochemicals are mainly expressed in the sensillum lymph of the antennae and assist in the adaptation of an insect to their hosts, which has been demonstrated across a diverse range of taxa (131)(132)(133). For example, it was found that An.…”
Section: Host Location and Adaptationmentioning
confidence: 99%
“…A living host of a particular insect can vary greatly based on its life history and feeding guilds, ranging from plants to other animals or humans. Insect OBPs involved in the recognition of host semiochemicals are mainly expressed in the sensillum lymph of the antennae and assist in the adaptation of an insect to their hosts, which has been demonstrated across a diverse range of taxa (131)(132)(133). For example, it was found that An.…”
Section: Host Location and Adaptationmentioning
confidence: 99%